Two‐dimensional gas chromatographic method for direct determination of formalin. Issue 6 (26th April 2019) - Tharpa, Kalsang; Diwakar, Makarand; Tantry, Sudha; Naidu, Kola S.; Rosa, A. D.; Deshpande, Raj
Abstract: A direct two‐dimensional gas chromatographic method is proposed for simultaneous determination of aqueous formaldehyde and other products present in the reaction sample. Using Deans switch, HCHO‐H2 O peak pair eluting from the first dimension column is heart cut into the second column where H2 O and HCHO are separated and quantified using thermal conductivity detection. Formaldehyde being a dissolved gas, the influence of the plunger speed on the repeatability was investigated. A reduction in the plunger speed from 300 (default) to 5 μL/min results in a major improvement in repeatability precision from 9.6 to 0.7 (RSD). The method is being used to quantify initial and final amount of HCHO in the range 0.02–0.36 g/g, along with other reaction products. The proposed method is validated by analyzing three commercial aqueous formaldehydes using two different techniques: USP29‐NF24 (by titrimetry) and derivatization method involving HCHO‐2, 4‐dinitrophenylhydrazine derivative on a high‐performance liquid chromatography with UV detection system.